A history outline of senior football of Raków Częstochowa Workers Sports Club in the years 1998-2023 - Krzysztof Kościański (Jan Długosz University in Częstochowa, 2024)
The club was founded in 1921. At that time, on the initiative of Marian Federak, Klub Sportowy Racovia was established. With the incorporation of the settlement of Raków into Częstochowa (1928), it changed its name to Raków Częstochowa. Its history was continuedboth in the interwar period, World War II and after the war. In the years 1998-2023, Robotniczy Klub Sportowy Raków Częstochowa was the most successful team from the Częstochowa region. After relegation from the first league in the 1997/1998 season, due to the result of organizational mistakes, the club was in debt. This was largely influenced by the financial problems of Huta Częstochowa. It had been themain sponsor of Raków for several decades. At the beginning of the 20th century, during one of the reporting and election meetings, a proposal was made to liquidate the club. However, this solution was postponed until a new association was prepared, which would formallymaintain the continuity of the sports team. In 2002, the Raków Klub Sportowy was established, continuing the tradition of RKS Raków. A few years later, another crisis occurred and the specter of collapse reoccurred (2009). A group of former Raków players gathered then, including Jerzy Brzęczek and Krzysztof Kołaczyk, who managed to stabilized the situation thanks to their actions. They acquired a new main sponsor, the company X-KOM. This enabled the association to be transformed into a joint-stock company (2011). From 2014, Michał Świerczewski became the owner of the club. Due to poor sports results, in 2016 he hired Marek Papszun as the first coach. In the following years, the Raków team achieved more and more sports successes, and in the 2022/2023 season they won the Ekstraklasa and won thetitle of Polish champion.